Incentives and anonymity principle : crowding out toward users - Patricia Crifo; Jean-Louis Rullière (Center for Economic Studies and ifo Institute (CESifo), 2004)
In our model, an agent produces an outcome by a costly effort and then distributes it among heterogeneous users. The agent's payoff is the weighted sum of the users? shares and the coefficient reflecting their heterogeneity. When the agent neglects users? heterogeneity the game leads to an anonymous allocation. Otherwise, the equilibrium distribution is non- egalitarian but more efficient. Low performing agents reduce inequality among users by delivering an egalitarian service, while intermediate or high performing agents tend to prefer (but not always) delivering an unequal service, thereby breaking the anonymity principle. Incentives do matter regarding the crowding effect toward users.
Keywords: L32; J45; J33; C9; M5; 330; incentives; anonymity principle; egalitarian tasks allocation; principal agent user relationship; crowding-out effect; Öffentliche Dienstleistung; Dienstleistungsqualität; Leistungsorientierte Vergütung; Agency Theory; Crowding out; Verbraucher; Spieltheorie; Theorie; Pencil-Pusher Game